Full value documentation in the Czech Food Composition Database - Machackova, M; Holasova, M; Maskova, E (European journal of clinical nutrition, 2010)
BACKGROUND/OBJECTIVES: The aim of this project was to launch a new Food Composition Database (FCDB) Programme in the Czech Republic; to implement a methodology for food description and value documentation according to the standards designed by the European Food Information Resource (EuroFIR) Network of Excellence; and to start the compilation of a pilot FCDB. SUBJECTS/METHODS: Foods for the initial data set were selected from the list of foods included in the Czech Food Consumption Basket. Selection of 24 priority components was based on the range of components used in former Czech tables. The priority list was extended with components for which original Czech analytical data or calculated data were available. Values that were input into the compiled database were documented according to the EuroFIR standards within the entities FOOD, COMPONENT, VALUE and REFERENCE using Excel sheets. Foods were described using the LanguaL Thesaurus. RESULTS: A template for documentation of data according to the EuroFIR standards was designed. The initial data set comprised documented data for 162 foods. Values were based on original Czech analytical data (available for traditional and fast foods, milk and milk products, wheat flour types), data derived from literature (for example, fruits, vegetables, nuts, legumes, eggs) and calculated data. CONCLUSIONS: The Czech FCDB programme has been successfully relaunched. Inclusion of the Czech data set into the EuroFIR eSearch facility confirmed compliance of the database format with the EuroFIR standards. Excel spreadsheets are applicable for full value documentation in the FCDB.
Keywords: Animals; vejce; Nuts; Vegetables; dokumentace; zelenina; Food Analysis; software; nutriční hodnota; Fabaceae; ořechy; Nutritive Value; databáze faktografické; Fruit; Milk; ovoce; analýza potravin; Czech Republic; Eggs; Software; Česká republika; Databases, Factual; zvířata; mléko; Documentation